Use of the child health clinic. Issue 6 (June 1981) - Hart, H; Bax, M; Jenkins, S
Abstract : Attendance at child health clinics in two areas of London, north Westminster and south Camden, is described. Routine examinations were attended by 97% of children although such visits accounted for only one-third of attendances. There were more non-routine visits than have been reported in most other studies–about 14 visits in Westminster and 12 in Camden during the first year. Over half the mothers sought advice on a wide variety of medical, developmental, and behavioural problems.